EVALUASI PEMERIKSAAN IMUNOKROMATOGRAFI UNTUK MENDETEKSI ANTIBODI IgM DAN IgG DEMAM BERDARAH DENGUE ANAK - Ety Retno Setyowati; Aryati Aryati; Prihatini Prihatini; M.Y. Probohoesodo (Indonesian Association of Clinical Pathologist and Medical laboratory, 2005)
The gold standard diagnosis of DHF by RT-PCR needs a complex technology and is time consuming. Serological tests have beendeveloped to detect IgM and IgG anti dengue to determine primary as well as secondary acute phase infection. IgM and IgG antidenguetests by immunochromatography have been used, due to a high diagnostic validity, also because they are simple, practicable, easy, rapid(15–30 minutes), can be used in a single serum sample. ELISA method has been used as a confirmation method. The aim of this studyis to evaluate the immunochromatography method in detecting IgG and IgM anti dengue of DHF patients. The study was performedon 50 serum samples from patients of the ICU Department of Paediatrics Dr. Soetomo Hospital, Surabaya during July–August 2005with dengue virus infection according to the 1997, WHO criterion and 27 serum samples from non dengue virus infection patients.ELISA method showed positive infection in 44 samples. Immunochromatography method showed positive infection in 43 samples, butwas negative in 1 sample. Diagnostic sensitivity of Immunochromatography is 97.7% (43/44) and the diagnostic specificity is 92.6%(25/27). Immunochromatography method has a high diagnostic value in assisting the diagnosis of DHF.